Post COVID symptoms in Patients of Cumilla District, Bangladesh - Amin, Al Amin; Hafsa, Najnin Jahan; Akter, Roksana; Shaha, Pinki; Roy, Utshab; Hasan, Nazmul; Saem, Abu Mohammad; Hoque, Mohammad Izazul (Journal of Comilla Medical College Teachers' Association, 2023)
Background: COVID-19 not only takes millions of lives and significant morbidities world wide but also retains significant post COVID symptoms. The COVID-19 pandemic has greatly impacted our psychosocial behaviors due to confinement, social distancing, masks and changes in working condition. Objective: The objective of our study is to evaluate the symptoms of post COVID-19 Patients in Cumilla district, Bangladesh. Methods: It was a retro-prospective observational study. All RT-PCR positive patients who tested in RT-PCR lab of Comilla Medical College in 10 days of each month from July to December 2020 were included in this study. 10 days in each month was selected by lottery. Selected patients were interviewed over telephone by the investigator team after getting the verbal consent and their information was recorded accordingly in a preformed data sheet. Results: Among 606 COVID-19 RT-PCR positive patients mean age was 40.39 ± 15.42 years, 62.8% were male. 97.2% recovered and 2.8% died. 33.8% patients suffered from post COVID symptoms. The most common symptoms were fatigue 73 (26.3%), Palpitation 67 (24.1%), muscle pain 24 (11.7%), CNS disturbance including depression 32 (15%), difficulty in breathing 15 (5.9%) and bodyache 13 (4.6%). Conclusion: Post COVID-19 is mainly characterized by musculoskeletal, pulmonary, neurological and digestive involvement including depression. More than one third of patients with COVID-19 report long-term symptoms 3 to 10 months after diagnosis. These data suggest that the post COVID symptoms placed a significant burden on society and especially healthcare systems. J Com Med Col Teachers Asso Jan 2023; 27(1): 14-18